(3cJGH Gdjbjfs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM GdKbI CHh GdMSf Ydi Hf CHj YHO Gddg Hf CHj GdMSf GdeDOH GdHZOGOi SeY CHGHcQ GdUOjb jbhd HYOeG bHV QShd Gddg Udi Gddg Ydjg hSde HSfg bGe ajfG s
(3BNQgG (B:s
(3hjQi hjSeY eG Cbhd aEf hKbJ agh caGfi BNQ GdLRA hddg GdMeO hGdefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HBNQgG SeGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1472s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs